Social Partnership Approach for Effective Social Worker Education - Tatyana S. Yeremeyeva; Andrei V. Leifa; Neile K. Schepkina; Natalya Y. Scheka; Mikhail P. Palyanov; Marina V. Morozova; Elena L. Rudneva; Nuriya Kh. Gzhemskaya (International Review of Management and Marketing, 2016)
The topic of the paper is relevant due to the current tendency in human, or social, service to turn to partnership methods in solving human problems, protecting the interests of certain social risk groups, and defining social development strategy - everything that makes social partnership an integral component of practical work, ensures that various organizations supporting social protection work provide proper and sufficient social services and care, and is considered as foundation for professional training in this sphere. The paper presents rationale for creating and evaluating organizational and pedagogical conditions (external and internal) while providing successful university training in social work and social care. It is intended for further development of occupational education in the sphere of social work through social partnership. The organizational and pedagogical conditions distinguished by the authors are able to contribute in optimization of the system of professional education and training, and provide the opportunity to develop social partnership and interdepartmental communication with various social institutions in the educational system.